Analysis of the Influence of Interpersonal Communication and Community Behavior on Tourist Security and its Impact on Tourist Visits to Samosir Island, North Sumatra - Indonesia - ., Rozaini; Lbn. Raja, Edward Alezandro; Lbn. Raja, Togu Harlen (Journal of Ecohumanism, 2025)
Samosir Island is a beautiful island where Samosir Island is surrounded by Lake Toba which is very beautiful by its lake and nature. The beauty of Lake Toba should contribute to the income of the community and the region, but the facts explain that the beauty of Lake Toba has not contributed to the income of the community and the region. This can be seen from the lack of tourists coming to Samosir Island for tourism. This is not comparable to the beautiful island of Bali which is visited by many local and foreign tourists so that it can contribute to the income of the community and the region. Based on this condition, it can be observed that there are several causes of the lack of tourists coming to Samosir Island such as interpersonal communication, community behavior, facilities and infrastructure so that they affect the comfort of tourism and have an impact on the number of tourist visits to Samosir Island. The type of research is quantitative research and the object of research is Samosir Island. The research respondents are the community around the tourist attractions on Samosir Island. The number of samples is 460 people taken based on random sampling. The research instrument used to collect data is a questionnaire that is distributed to the community randomly in the tourist area of ​​Samosir Island. To process the data, a Structural Equation analysis model is used (SEM). The results of the study explain that there is an influence between interpersonal communication on tourist comfort where the coefficient influence value is greater than the p-value or 0.398 > 0.000, there is an influence between community behavior on tourist comfort where the coefficient influence is greater than the p-value or 0.207 > 0.002, there is an influence between interpersonal communication on tourist visits where the coefficient influence is greater than the p-value or 0.287 > 0.000, there is an influence of community behavior on the number of tourist visits where the coefficient influence is greater than the p-value or 0.401 > 0.000, there is an influence between interpersonal communication on the number of tourist visits through tourist comfort where the coefficient influence is greater than the p-value or 0.265 > 0.000, there is an influence between community behavior on the number of tourist visits where the coefficient influence is greater than the p-value or 0.105 > 0.00 and there is an influence between tourist comfort on the number of tourist visits where the coefficient influence is greater than p-value or 0.055 > 0.003.